Assessment of a Socio-constructivist Model for Teacher Training - Luiz Antonio Joia (Arizona State University, 2002)
This article assesses a socio-constructivist model for training K-12 teachers in Brazil, in the use of Informatics in education. The method applied combines both face-to-face exchanges and a WEB-based distance approach made possible by Internet technology. The characteristics of such training and its main objectives are analyzed according to the collected data presented. A descriptive single case study research methodology is applied. The main conclusions reached by this research-based on the use of a systemic framework-are presented, mainly those addressing the importance of care and coherence for knowledge creation in a socio-constructivist training model developed with the help of the Internet. Comparisons between this model and the traditional one are also presented.